Is Emotional Intelligence Impaired in Unaffected Siblings of Patients with Schizophrenia?. (13th June 2017) - Frajo-Apor, Beatrice; Kemmler, Georg; Pardeller, Silvia; Huber, Markus; Macina, Christian; Welte, Anna-Sophia; Hofer, Alex
Abstract: Objectives: Social cognitive deficits have been discussed to be endophenotypes for schizophrenia and other serious mental illnesses. The current study aimed to assess emotional intelligence (EI) in unaffected siblings of schizophrenia patients to investigate its potential role as endophenotype for schizophrenia.Methods: EI was measured in 56 schizophrenia patients, 57 unaffected siblings, and 127 healthy control subjects by using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT). In addition, non-social cognition was assessed with the Brief Assessment of Cognition in Schizophrenia (BACS). Linear mixed models with compound symmetric correlation structure were used for of the three groups with respect to EI and non-social cognition.Results: Schizophrenia patients showed significantly lower overall EI and performed significantly worse in three out of four MSCEIT branches compared to unaffected siblings and control subjects, whereas the two latter groups had comparable EI levels. Similar performance patterns (patients<unaffected siblings=control subjects) were found with respect to non-social cognition. Solely in the "Tower of London" test, siblings achieved significantly lower task scores compared to control subjects.Conclusions: Based on our results, EI as measured with the MSCEIT does not seem to represent a marker of risk for schizophrenia. Further investigations should concentrate on other EI measures to reassess this finding. ( JINS, 2017, 23, 577–583)